Aggregate costs of gender gaps in the labor market: a quantitative estimate - Teignier, Marc (Barcelona, 2014)
"This paper examines the quantitative effects of gender gaps in entrepreneurship and labor force participation on aggregate productivity and income per capita. We simulate an occupational choice model with heterogeneous agents in entrepreneurial ability, where agents choose to be workers, self-employed or employers. The model assumes that men and women have the same talent distribution, but we impose several frictions on women's opportunities and pay in the labor market. In particular, we restrict the fraction of women participating in the labor market. Moreover, we limit the number of women who can work as employers or as self-employed and, finally, women who become workers receive a lower wage. Our model shows that gender gaps in entrepreneurship and in female workers' pay affect aggregate productivity negatively, while gender gaps in labor force participation reduce income per capita. Specifically, if all women are excluded from entrepreneurship, average output per worker drops by almost 12% because the average talent of entrepreneurs falls down, while if all women are excluded from the labor force income per capita is reduced by almost 40%. In the cross-country analysis, we find that gender gaps and their implied income losses differ importantly across geographical regions, with a total income loss of 27% in Middle East and North Africa and a 10% loss in Europe."